Pico de velocidade de crescimento como alternativa para classificação maturacional associada ao desempenho motor - Machado, Dalmo Roberto Lopes [UNESP]; Bonfim, Mariana Rotta [UNESP]; Costa, Leonardo Trevizan [UNESP] (FapUNIFESP (SciELO), 2009)
Adolescence is a phase characterized by important physical and maturational alterations, with individuals of the same chronological age, but who are more mature, may present sportive advantages because of greater force gain and additional muscle mass. Thus, in studies evaluating motor skills of children and adolescents, maturational classification should be an efficient and easily applicable tool in order to facilitate the interpretation of the true relationship between maturation and motor performance. Therefore, the objective of this study was to compare the relationship between motor performance and different types of classification of biological maturation in 209 boys aged 6 to 17 years (11.59 ± 2.57) practicing soccer. Anthropometric variables were obtained according to the ISAK criteria. Biological maturation was determined based on age at peak height velocity (PHV) and also by self-assessment of sexual maturation (genitalia and pubic hair). Motor performance was evaluated by sit-and-reach tests, horizontal jump, modified push-ups, 50-m run, and 9/12-min run/walk. The results showed progression in the variables analyzed as the subjects reached maturity. Correlation analysis and the regression values indicated higher consistency for the PHV classification, which better explained motor performance according to maturational status, exceeding the values obtained by comparison according to age or sexual maturation. Thus, the use of PHV as a biological classification instrument is preferably recommended for youngsters with characteristics similar to those of the present sample.
Peak height velocity as an alternative for maturational classification associated with motor performance
Keywords: Adolescent; Maturation; Motor activity; Soccer